Efficacy of photodynamic therapy as an adjunct to conventional endodontic treatment in the disinfection and microbial control of root canals (Research, Society and Development, 2026)
Endodontic treatment is used to prevent and treat diseases of pulpal and periapical origin. Its success is also directly linked to the maximum elimination of microbial infection in the root canal system (RCS), whose anatomical complexity imposes limitations on conventional chemomechanical preparation (CMP), allowing the persistence of pathogens, which leads to treatment failures. Therefore, this study aimed to evaluate the effectiveness of Antimicrobial Photodynamic Therapy (aPDT) as an auxiliary method in the disinfection and microbial control protocol of root canals. Data collection was carried out in the PubMed, SciELO, and LILACS databases (accessed through the Virtual Health Library), using the descriptors "Photodynamic Therapy", "Root Canal", "Disinfection", and "Endodontics". The inclusion criteria adopted were: articles published in the last five years, in English, Portuguese, or Spanish, full text and free of charge, and within the investigated theme. According to the articles analyzed, it was found that PDT acts by activating a photosensitizer by light in the presence of oxygen, generating Reactive Oxygen Species (ROS) that cause lethal oxidative damage to microorganisms. The results show that the application of PDT, in addition to PQM, significantly enhances disinfection, being highly effective in eliminating bacteria in biofilms and resistant strains, even in hard-to-reach areas. It is concluded that Antimicrobial Photodynamic Therapy is a safe, minimally invasive tool, whose incorporation into the clinical protocol is capable of overcoming the limitations of the traditional method, contributing to increased success rates in endodontic treatment.